Pendugaan Potensi Air Tanah di Jorong Siparayo, Nagari Malampah Menggunakan Metode Geolistrik Konfigurasi Wenner - Adelia Orenza Oktavia; Akmam Akmam; Ahmad Fauzi; Zulhendra Zulhendra (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Jorong Siparayo, Nagari Malampah, relies on groundwater as its primary source of clean water due to limited surface water availability. Following the 2022 earthquake, damage to the water supply infrastructure increased the community's dependence on shallow dug wells and boreholes equipped with pumping systems, while information on aquifer distribution and groundwater potential remains limited. This study aims to identify aquifer zones and assess groundwater potential using the Wenner array. Primary geoelectrical data were acquired using the Automatic Resistivity System (ARES) and processed using the Least-Squares inversion method in Res2DInv software. Data interpretation integrated regional geological information with reference resistivity values to infer subsurface lithology and groundwater potential. The results indicate that aquifer zones are characterized by resistivity values of 20–90 Ωm, corresponding to water-saturated sand and gravel layers at depths of approximately 4–32 m. Several aquifer zones are interpreted as confined aquifers, suggesting potential for artesian well development. This study contributes by providing an interpretation of confined aquifer zones through the integration of geoelectrical resistivity data and regional geological information as a basis for estimating the potential for artesian wells.